VAT on the Sale to Individuals of E-commerce Goods Held in Customs Warehouses in the EEU - A. A. Artemiev; E. Yu. Sidorova (Финансы: теория и практика, 2024)
The relevance of the study is due to the fact that in the context of the spread of new models of business organization, including foreign trade transactions with electronic commerce goods (ECG) purchased by individuals on foreign electronic trading platforms, it is necessary to develop issues related to the determination of tax consequences for persons — participants of such models. The term “goods” in this study means any movable property, including currency of the member states of the Eurasian Economic Union (EEU), securities and (or) currency values, travel cheques, electricity, as well as other movable things equated to immovable property. Since the value added tax (VAT) is one of the most significant for both the state and taxpayers (tax agents), the subject of the study is the mechanism for determining the tax consequences of VAT when foreign sellers sell to Russian individuals electronic commerce goods (ECG) purchased through foreign trading platforms (“marketplaces”), while being (stored) at the time of conclusion of the contract of sale in customs warehouses in Russia. The purpose of the study is to solve the problems related to the determination of VAT payment obligations in connection with the sale of ECG stored in a customs warehouse, namely: economic aspects related to the grounds for the emergence of VAT payment obligations, and the feasibility of changes in the current regulation with regard to the possible consequences. The methodology of the study is based on the use of classical for indirect taxation approaches to the determination of the place of sale of goods and, accordingly, to the decision on the occurrence in the territory of Russia of the object of taxation by the VAT. The scientific novelty of the study consists in the development of approaches to the determination of tax consequences on VAT on the sale of goods from the territories of customs warehouses within the framework of cross-border electronic commerce, as well as possible changes in the current regulation, based on the consideration of the economic sense of the considered business model. It is concluded that when a foreign seller sells goods to Russian individuals through a “marketplace” that are stored in a customs warehouse on the territory of Russia during the purchase period, the seller is subject to VAT. A person of an EAEU member state (Russian organization) — an e-commerce operator — who transfers goods to a purchaser is obliged to present to the purchaser the corresponding amount of VAT, performing the duties of a tax agent. Proposals on the establishment of VAT concessions for transactions on the implementation of ECG from the territory of the customs warehouse were elaborated, the results concluded that the discussion and insufficient economic justification of such proposals.